Political Stance Using Deixis in Annalena Baerbock’s United Nations Speech - Muhammad Zulfan Adi Putra; Ruminda Ruminda; Toneng Listiani (Journal of English Language and Education, 2026)
Deictic expressions constitute a fundamental pragmatic mechanism in political communication, yet their role in constructing diplomatic stances within multilateral forums remains underexplored. This study aims to examine how deictic expressions are employed to construct political stance in the closing remarks delivered by Annalena Baerbock, President of the 80th session of the United Nations General Assembly, at the Closing of the General Debate on 29 September 2025 in New York. Employing a descriptive qualitative approach, the data were collected through purposive sampling across three discursive domains: global geopolitical crises, the climate change crisis, and women's rights and gender equality. The data were analyzed using Levinson's (1983) five-type deixis framework and mapped onto Du Bois's (2007) Stance Triangle. The findings reveal that person deixis is the most dominant category, functioning as the primary resource for evaluation, positioning, and alignment. Collectively, deictic expressions serve as a unified rhetorical instrument that transforms bureaucratic discourse into a morally binding call for global action.